2015
DOI: 10.1016/j.aml.2014.12.001
|View full text |Cite
|
Sign up to set email alerts
|

A generalized shift-splitting preconditioner for saddle point problems

Abstract: Abstract. In this paper, the generalized shift-splitting preconditioner is implemented for saddle point problems with symmetric positive definite (1,1)-block and symmetric positive semidefinite (2,2)-block. The proposed preconditioner is extracted form a stationary iterative method which is unconditionally convergent. Moreover, a relaxed version of the proposed preconditioner is presented and some properties of the eigenvalues distribution of the corresponding preconditioned matrix are studied. Finally, some n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(27 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…From the numerical examples in [42], we find the eigenvalues distribution of the preconditioned matrix P −1 GSS A gather more closely than those in [41], also the convergence performance is better.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…From the numerical examples in [42], we find the eigenvalues distribution of the preconditioned matrix P −1 GSS A gather more closely than those in [41], also the convergence performance is better.…”
Section: Introductionmentioning
confidence: 79%
“…The experiments have been carried out by MAT-LAB R2011b (7.13), Intel(R) Core(TM) i7-2670QM, CPU 2.20GHZ, RAM 8.GB PC Environment. Especially, when C = 0, i.e., the 2-by-2 block of the coefficient of (1.1) is zero, we compare the MPSS preconditioner with the RPSS in [43], GSS in [42] and no preconditioning situation. [4], the coefficient matrix have the following form…”
Section: Numerical Experimentsmentioning
confidence: 99%
“…It is easy to see that P SS is a special case of P GSS when α = β. Numerical results in [21,20] confirmed that the GSS preconditioner is superior to the SS preconditioner.…”
mentioning
confidence: 77%
“…And Krylov subspace methods are very slow or even fail to converge if not conveniently preconditioned. Therefore, many researchers devote themselves to the preconditioned iterative methods (1.1) (see [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]). And kinds of preconditioners for saddle point matrix are studied, such as symmetric indefinite preconditioners [28,29], inexact constraint preconditioners [29][30][31][32][33][34] and primal-based penalty preconditioners [35].…”
Section: Introductionmentioning
confidence: 99%